Analisis Nilai Panca Jiwa di Pondok Pesantren Modern dan Kaitannya Dengan Nilai Pendidikan Karakter Bangsa - Wahyudi, M. Iman; Kurniawan, Ade Fakih; Lazzavietamsi, Fandy Adven Fandy Adpen (Lembaga Yasin AlSys, 2021)
The expected of national education goals are stated in the National Education System Law no. 20 of 2003 is to educate the student to be human beings who has believe in God, fear of God Almighty, have noble character, healthy, knowledgeable, capable, creative, independent, become democratic and also responsible citizens. This paper describes how the implementation of the Panca Jiwa of modern Islamic boarding schools in education is carried out by teachers (ustadz and ustadzah) at Modern Islamic Boarding Schools. The results that obtained from this analysis are; Modern Islamic Boarding Schools with the implementation of the Panca Jiwa Pondok have implemented as good as possible to build students’ character or what is called by the instilling of moral values to their students as proclaimed by the 2003 National Education System Constitution.